The Reducing Hospital Costs through Horizontal Integration - Staňková, Pavla; Papadaki, Šárka; Dvorský, Ján (Iranian journal of public health, 2019)
BACKGROUND: This paper investigated the impact of hospitals' horizontal integration in the Czech Republic on the cost behavior. The aim of the research was to examined the hospitals costs in specific environment of region hospitals at NUTS 3 level (Nomenclature of Units for Territorial Statistics) - Administrative Regions. METHODS: The survey was conducted in the period from April to August 2016 in the Czech Republic. The research was divided into two parts. The first part was based on data obtained from the Institute of Health Information and Statistics of the Czech Republic. We used Statgraphics Centurion XVII for the descriptive statistics and data visualization. Second part of the results was obtained through a survey research focused on managers of the horizontal integrated hospitals and their experiences with the cost behavior. RESULTS: The results from statistical survey showed that up to 80 percent of the observed region hospitals at NUTS 3 level, the cost of treatment for a patient per day has decreased after integration into an association. Based on primary survey, 73% hospital managers confirm these results and see one of the advantages that it is possible to reduce costs through integration of hospitals. The largest savings, according to hospital managers, are due to central purchasing and investments, together and they have a better negotiation position with suppliers. CONCLUSION: We can confirm that horizontal integration of hospitals can lead to reduction of costs and higher efficiency, in the specific environment of region hospitals at NUTS 3 level.
Keywords: Cost reduction; Horizontal integration; Hospitals; Costs; Effectiveness